Development of Electronic Modules Using the Canva Application Assisted with Quizizz in Learning Achievements Basic Accounting Principles and Concepts - Widiastuti, Ayu; Widayati, Ani (East Asian Journal of Multidisciplinary Research, 2024)
The objectives of this research are: (1) creating learning media in the form of electronic modules for students; (2) explain the feasibility of learning media in the form of electronic modules created based on the opinions of material experts and media experts; (3) reveal the practicality of learning media in the form of electronic modules based on the opinions of educational practitioners/teachers and users/students. This research is development research using the ADDIE development model. The test subjects in this research were classes X AKL1 and X AKL2 at Muhammadiyah Dukun Vocational School. Data was collected through observation and questionnaires. This research uses quantitative descriptive analysis. The data collection instrument used was a verification questionnaire from material expert validators, media expert validators, teachers and student responses.